Gait Pattern Analysis Through Various Techniques and Methods - A Review (International Journal of Scientific Research in Science and Technology, 2024)
The gait cycle, which involves propelling the centre of gravity in the direction of motion, is the interval of time or series of action during locomotion from the moment one foot touches the ground to the moment that same foot contact the ground again. Examination of person’s waking style or standing and walking pattern called gait analysis. The result of this analysis can be used to determine the causes skeletal muscular Examination or neurological issues, as well as it is applicable in criminal investigation to find out the unique gait pattern of an individual by using the different parameters and technique.